Complementary Medicine and Self-Care Strategies in Women with (Recurrent) Urinary Tract and Vaginal Infections: A Cross-Sectional Study on Use and Perceived Effectiveness in The Netherlands - Louise Witteman; Herman A. van Wietmarschen; Esther T. van der Werf (MDPI AG, 2021)
Due to the excessive use of antibiotic and antimycotic treatments, the risk of resistant microbes and fungi is rapidly emerging. Previous studies have demonstrated that many women with (recurrent) urinary tract infection (UTI) and/or vaginal infections (VIs) welcome alternative management approaches to reduce the use of antibiotics and antifungals and avoid short- and long-term adverse effects. This study aims to determine which complementary medicine (CM) and self-care strategies are being used by women suffering from (recurrent) UTI and VI in The Netherlands and how they perceive their effectiveness in order to define directions for future research on safety, cost-effectiveness, and implementation of best practices. A cross-sectional online survey was performed among women, ≥18 years old, with a history of UTIs; 162 respondents were included in the data analysis, with most participants aged between 50 and 64 years (36.4%). The women reported having consulted a CM practitioner for UTI-specific symptoms (23.5%) and VI-specific symptoms (13.6%). Consultations of homeopaths, acupuncturists, and herbal physicians are most often reported. Overall, 81.7% of the women suffering from UTI used complementary or self-care strategies besides regular treatment, and 68.7% reported using CM/self-care strategies to treat vaginal symptoms. UTI- related use of cranberries (51.9%), vitamin C (43.8%), and D-mannose (32.7%) were most reported. Perceived effectiveness was mostly reported for homeopathic remedies and D-mannose. The results showed a substantial burden of UTI and VI on daily and sexual activities. Besides the frequency of use, the indication of perceived effectiveness seems to be an important parameter for further and rigorously designed research to encourage nonantibiotic/antifungal treatment implementation into daily clinical practice.